Warship under sail : the USS Decatur in the Pacific West - McConaghy, Lorraine (Emil and Kathleen Sick lecture-book series in western history and biography, 2009)
A social history of the nineteenth-century sloop of war "Decatur," that illuminates American expansionism in the antebellum Pacific Northwest